Rocky start for wearables in professional sports games - Waltz, E. (IEEE Spectrum, 2016)
Major League Baseball (MLB) has approved two wearable biometric devices for use during games. Players will be allowed to wear the Motus baseball sleeve, which tracks strain on pitching arms, and the movement-tracking Zephyr bioharness during the 2016 season. The organization had previously remained silent on the issue. Meanwhile, the National Basketball Association (NBA) last week reprimanded a player for wearing the Whoop wristband, which, along with all wearables, is banned during NBA games. The contrasting league policies, along with some ambiguity about what exactly is allowed, has resulted in a rocky start for the niche market for wearables tailored for elite athletes.